2010
DOI: 10.1177/0021943610364516
|View full text |Cite
|
Sign up to set email alerts
|

Communicating Corporate Ethos on the Web: The Self-Presentation of PR Agencies

Abstract: This research examines credibility in the discourse offered on the corporate Web sites of 60 British, Danish, and Norwegian public relations (PR) agencies. This study's purpose was to see whether the North European PR industry moves in the direction of convergence or divergence in their corporate self-presentations. The authors have done this by unfolding the rhetoric and language of PR agencies Web sites. In this process, this study tried to determine whether the rhetorical strategies they use to achieve cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The next step was to establish a criterion for the selection of company websites. As pointed out in Isaksson and Jørgensen (2010, p. 128), who studied the websites of public relations companies, it is very difficult to “develop [ . .…”
Section: Methodological Issues and Data Collectionmentioning
confidence: 99%
“…The next step was to establish a criterion for the selection of company websites. As pointed out in Isaksson and Jørgensen (2010, p. 128), who studied the websites of public relations companies, it is very difficult to “develop [ . .…”
Section: Methodological Issues and Data Collectionmentioning
confidence: 99%
“…Aristotle's ethos framework has been used productively by other business communication scholars in previous studies (Beason, 1991;Eckhouse, 1999;Griffin, 2009;Hyland, 1998;Isaksson & Jørgensen, 2010;Kallendorf & Kallendorf, 1985;Stoddard 1985;Williams, 2008;Walzer, 1981). The framework can be particularly useful in a specific case of leader communication for both methodological and practical purposes.…”
Section: B Research Inquirymentioning
confidence: 99%
“…Of the three modes of persuasive appeals, Aristotle considered ethos, which addresses judgments of speaker credibility, most important (Aristotle, 2007, p. 39). Additionally, many business communication scholars have argued for the relevance of ethos to business communication (Beason, 1991;Eckhouse, 1999;Griffin, 2009;Hyland, 1998;Isaksson & Jørgensen, 2010;Kallendorf & Kallendorf, 1985;Stoddard 1985;Williams, 2008;Walzer, 1981 and its relevance to crisis communication. Griffin (2009) found that ethos appeals were important for maintaining a positive corporate identity during a crisis and showed how Merck tried to develop a corporate identity of "understanding, sympathy, and trust" through public letters.…”
Section: A Ethos In Business Communicationmentioning
confidence: 99%
See 2 more Smart Citations